Taxonomic Synopsis of Eriosema (Leguminosae: Papilionoideae, Phaseoleae) in Brazil - Cândido, Elisa Silva; de Vargas, Wanderleia; Bezerra, Luísa Maria De Paula Alves; Mansano, Vidal De Freitas; Vatanparast, Mohammad; Lewis, Gwilym Peter; Tozzi, Ana Maria Goulart De Azevedo; Fortuna-Perez, Ana Paula (Phytotaxa, 2019)
Eriosema is a pantropical genus occurring mostly in savanna vegetation and grasslands of tropical environments, with approximately 150 species and two centers of diversity, one in Africa with about 110 species, and the other in the Neotropics with about 40 species. Considering the large number of Eriosema taxa in Brazil, including five recently described, and the lack of recent study that encompasses all species that occur in the country, a taxonomic synopsis of the Brazilian species of Eriosema was needed and is presented here. Herbaria collections, including type specimens, were consulted and field work was carried out in Brazil. Our study records 35 Eriosema species in Brazil, which concentrates most of the diversity of the genus in the Americas (85%; 35 out of 41 species). Most of this diversity occurs in the Central Brazilian savannas, particularly in the states of Goiás (29 taxa, eight endemic), and Minas Gerais (26 taxa, four endemic). Among all American species in the genus, Eriosema simplicifolium and E. crinitum have the broadest geographical distributions, and occur throughout Brazil and most part of the American continent. They form species complexes and future detailed studies will be necessary in order to understand taxon boundaries and delimitations. An identification key, taxon descriptions, information about type specimens as well as information on the habitat, phenological and geographical records, together with distribution maps, images of representative species in the field and the main morphological characters are provided to assist in the correct identification of this group of savanna plants. We also present 15 lectotypifications, out of which three are second-step.